2016
DOI: 10.1111/andr.12211
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to endocrine disrupting chemicals and neurodevelopmental alterations

Abstract: SUMMARYThe developing brain is remarkably malleable as neural circuits are formed and these circuits are strongly dependent on hormones for their development. For those reasons, the brain is very vulnerable to the effects of endocrine-disrupting chemicals (EDCs) during critical periods of development. This review focuses on three ubiquitous endocrine disruptors that are known to disrupt the thyroid function and are associated with neurobehavioral deficits: polychlorinated biphenyls, polybrominated diphenyl eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
10

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 170 publications
0
27
0
10
Order By: Relevance
“…Our review found “sufficient evidence of toxicity” based on diminished intelligence associated with increased exposure to PBDEs, and “limited evidence of toxicity” based on increases in ADHD and attention-related behaviors with increased exposure to PBDEs. We identified nine reviews of this topic published between 2003 and 2016 ( Berghuis et al 2015 ; Brandt 2012 ; Chao et al 2014 ; De Cock et al 2012 ; Kim et al 2014 ; Muir 2003 ; Pinson et al 2016 ; Roth and Wilks 2014 ; Vrijheid et al 2016 ), none of which conducted a meta-analysis or consistently applied all nine components of a systematic literature review as described in the Literature Review Appraisal Toolkit (LRAT), a tool derived from a number of standard practice appraisals of the methodological quality of the literature reviews conducted in the medical sciences (see http://policyfromscience.com/lrat/ ) ( Ades et al 2012 ; Garg et al 2008 ; Higgins and Green 2011 ; Moher et al 2009 ; Mulrow 1987 ; Oxman et al 1994 ; Schulz et al 2010 ; Shea et al 2007 ). Broadly, our results that PBDEs are associated with adverse neurodevelopment (either directly or indirectly, e.g, as a thyroid hormone disruptor), were generally consistent with the findings of all but one of the nine reviews ( Roth and Wilks 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our review found “sufficient evidence of toxicity” based on diminished intelligence associated with increased exposure to PBDEs, and “limited evidence of toxicity” based on increases in ADHD and attention-related behaviors with increased exposure to PBDEs. We identified nine reviews of this topic published between 2003 and 2016 ( Berghuis et al 2015 ; Brandt 2012 ; Chao et al 2014 ; De Cock et al 2012 ; Kim et al 2014 ; Muir 2003 ; Pinson et al 2016 ; Roth and Wilks 2014 ; Vrijheid et al 2016 ), none of which conducted a meta-analysis or consistently applied all nine components of a systematic literature review as described in the Literature Review Appraisal Toolkit (LRAT), a tool derived from a number of standard practice appraisals of the methodological quality of the literature reviews conducted in the medical sciences (see http://policyfromscience.com/lrat/ ) ( Ades et al 2012 ; Garg et al 2008 ; Higgins and Green 2011 ; Moher et al 2009 ; Mulrow 1987 ; Oxman et al 1994 ; Schulz et al 2010 ; Shea et al 2007 ). Broadly, our results that PBDEs are associated with adverse neurodevelopment (either directly or indirectly, e.g, as a thyroid hormone disruptor), were generally consistent with the findings of all but one of the nine reviews ( Roth and Wilks 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Bu işlem engellenir ise, nörogelişimsel bozukluklar ortaya çıkabilmektedir. 22 Memeli beyin gelişimi, tam olgunlaşmaya eriş-meden önce çeşitli içsel gelişim süreçlerini ve aşa-malarını içermektedir. Beyin gelişme süreci (BGS) olarak adlandırılan bu dönem, aksonal ve dendritik büyüme, sinaptogenez, glial çoğalma, miyelinasyonun olgunlaşması ve nöral bağların kurulması gibi birçok kritik gelişimsel değişikliğin görüldüğü ve zararlı kimyasal maddelere maruziyet açısından hassas bir süreçtir.…”
Section: Beyi̇n Geli̇şi̇mi̇ Ve Bi̇li̇şsel Fonksi̇yonlar üZeri̇ne Etki̇leri̇unclassified
“…Since the beginning of the 2000s, studies started to focus on prenatal to postnatal exposure to environmental agents as non-genetic risk factors. Early development is a recognized window of susceptibility to external cues, which can have detrimental effects, potentially modulating the neuropathological events that lead to the onset of the disorder (21). To infer associations between Table 1: Data regarding characteristics of the ASD-and control population datasets used in this study.…”
Section: Introductionmentioning
confidence: 99%